2005
DOI: 10.1111/j.1365-2672.2004.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall modifications during osmotic stress in Lactobacillus casei

Abstract: M . P I U R I , C . S A N C H E Z -R I V A S A N D S . M . R U Z A L . 2004.Aims: To study the modification of the cell wall of Lactobacillus casei ATCC 393 grown in high salt conditions. Methods and Results: Differences in the overall structure of cell wall between growth in high salt (MRS + 1 mol l )1 NaCl; N condition) and control (MRS; C condition) conditions were determined by transmission electronic microscopy and analytical procedures. Lactobacillus casei cells grown in N condition were significantly la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 33 publications
7
81
1
Order By: Relevance
“…Quantitative studies indicated, however, that the amounts of compatible solutes produced by E. coli may not be sufficient to maintain cell turgor exclusively based on increasing intracellular osmolality, implying accompanying effects such as molecular crowding 14 . Besides adjusting intracellular osmolality, other bacteria have been shown to modify their cell wall structure upon osmotic stress 5 , but this mechanism has not been observed in E. coli. Virtually all known osmoprotection mechanisms in E. coli therefore relate to the modulation of intracellular osmolality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies indicated, however, that the amounts of compatible solutes produced by E. coli may not be sufficient to maintain cell turgor exclusively based on increasing intracellular osmolality, implying accompanying effects such as molecular crowding 14 . Besides adjusting intracellular osmolality, other bacteria have been shown to modify their cell wall structure upon osmotic stress 5 , but this mechanism has not been observed in E. coli. Virtually all known osmoprotection mechanisms in E. coli therefore relate to the modulation of intracellular osmolality.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences are changing cellular volume and turgor pressure that exert strong mechanical forces on the cytoplasmic membrane and associated proteins and, if too high, preclude growth of the bacterium and eventually cause cell death 1 . To cope with osmotic stress, bacteria evolved several strategies such as adapting their intracellular osmolality [2][3][4] or increasing their cell wall stability 5 , allowing them to grow in a broad range of solute concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying for several years the biochemical and biophysical characteristics of the cell envelopes of cells grown under osmotic stress both in B. subtilis and in Lactobacillus casei (Ló pez et al, , 2001(Ló pez et al, , 2002Piuri et al, 2003;Machado et al, 2004;Piuri et al, 2005). In these studies, the analysis of membrane lipids has revealed that there is a significant increase in the anionic lipid fraction such as phosphatidylglycerol (PG) and especially cardiolipin (CL) when B. subtilis cells are grown in LB medium containing 1?5 M NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, significant enlargement of cells under high ionic stress was observed in Lactobacillus casei 15) and Staphylococcus aureus. 16) To investigate the relationship between salt-stressed culture conditions and cell size, bacterial cell sizes were measured by a particle size analyzer, SALD-2200.…”
Section: Cell-size Determinationmentioning
confidence: 99%
“…13) It is well-known that bacterial cell sizes are increased when they are grown in complex media containing high concentrations of NaCl. [14][15][16] The enlargement of cell size is due to a decrease in peptidoglycan cross-links in the cell wall. There have been a few studies on the influence of cell components (cell wall and cell plasma fraction) on the LAB stimulating immune system.…”
mentioning
confidence: 99%